Citizens’ Perception on Effects of Kidnapping on Security in Edo South Senatorial District (British Journal of Multidisciplinary and Advanced Studies, 2024)
The cases of kidnapping in Nigeria and in Edo State in particular are rising, and taking dangerous dimensions. What exists in the literature is an ample of research reports on the causes and socioeconomic implications of kidnapping. The general objective of this study is to explore citizens’ perception of the effects of the rising incidence of kidnapping on the security situations in Edo South Senatorial District of Edo State. The exploratory research design operated with the cross sectional research design was adopted for this study.  The calculated sample size for this study was placed at approximately 816. For the collection of qualitative data, the purposive sampling techniques were used to select two interviewees from each of the local government areas. Hence, there were 14 interviewees for the collection of qualitative data that complemented the quantitative data. The majority of respondents (54.7%) believe that the death of victims during kidnappings is avoidable or preventable. There was statistically significant difference in the perception of the level of panic due to kidnapping in Edo South according to the age groups. There is statistically significant association between educational qualification and the tendency to get the Police involved in cases of kidnapping. There was statistically significant difference in perceived police effectiveness in the fight against kidnapping in Edo South according the respondents’ nature of employment. In conclusion, there is a significant number of people who are concerned about kidnapping in their area, with most of affirming a high level of panic due to kidnapping. Kidnapping has a negative impact on society and is a source of fear and concern for many people. The lack of proper security measures adds to the problem, and people are left to take precautions to avoid being kidnapped. The citizens are adjusting to the panic caused by kidnapping by taking practical measures to ensure their safety and seeking solace through spiritual practices. It is recommended that the police should take proactive measures to prevent kidnappings, have the necessary resources and training to handle kidnapping cases, and work with other security agencies and organizations to provide support and services to victims after their release.